2013
DOI: 10.1063/1.4794422
|View full text |Cite
|
Sign up to set email alerts
|

On the kinetics of MoSe2 interfacial layer formation in chalcogen-based thin film solar cells with a molybdenum back contact

Abstract: We have studied the temperature dependent kinetics of MoSe2 formation between molybdenum and Cu2ZnSnSe4 (CZTSe) films during annealing in the presence of Se. CZTSe is an emerging light-absorbing material for thin film solar cell applications, and thermal treatment of this layer constitutes a critical part of the device processing. The formation of MoSe2 in this system is modeled using a three step mechanism—diffusion of Se through CZTSe, diffusion of Se through MoSe2, and reaction between Se and Mo. Applying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
84
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(87 citation statements)
references
References 10 publications
1
84
0
2
Order By: Relevance
“…Reflexes originating from the kesterite phase are marked with red circles and additional reflexes at 31.6° and 56.5° indicate Mo(S,Se) 2 . [26] The Sn(S,Se) 2 secondary phase can be identified from the XRD patterns of samples with 33.3% nominal Sn content and more. Other secondary phases cannot be distinguished, however Zn(S,Se) and Cu 2 Sn(S,Se) 3 cannot be excluded since their reflexes coincide with those of CZTSSe.…”
Section: Resultsmentioning
confidence: 99%
“…Reflexes originating from the kesterite phase are marked with red circles and additional reflexes at 31.6° and 56.5° indicate Mo(S,Se) 2 . [26] The Sn(S,Se) 2 secondary phase can be identified from the XRD patterns of samples with 33.3% nominal Sn content and more. Other secondary phases cannot be distinguished, however Zn(S,Se) and Cu 2 Sn(S,Se) 3 cannot be excluded since their reflexes coincide with those of CZTSSe.…”
Section: Resultsmentioning
confidence: 99%
“…[ 6 ] It is reported that the Mo/CZTSSe interface is not as chemical stable as the Mo/CIGS interface. [7][8][9] The interfacial MoSe 2 does not appear in coevaporated CZTSe solar cells because of the low Se partial pressure in co-evaporation process; [ 10,11 ] however, the overthick interfacial MoS 2 /MoSe 2 layer is currently a serious and prevalent problem in CZTSSe solar cells fabricated by post annealing approaches. [ 8,9,12,13 ] The overthick MoSe 2 will reduce the thickness of Mo layer dramatically and deteriorate the electrical contact of CZTSe to Mo substrate, both of which will increase the series resistance of the device signifi cantly.…”
Section: Doi: 101002/aenm201402178mentioning
confidence: 99%
“…[7][8][9] The interfacial MoSe 2 does not appear in coevaporated CZTSe solar cells because of the low Se partial pressure in co-evaporation process; [ 10,11 ] however, the overthick interfacial MoS 2 /MoSe 2 layer is currently a serious and prevalent problem in CZTSSe solar cells fabricated by post annealing approaches. [ 8,9,12,13 ] The overthick MoSe 2 will reduce the thickness of Mo layer dramatically and deteriorate the electrical contact of CZTSe to Mo substrate, both of which will increase the series resistance of the device signifi cantly. [ 8 ] In order to reduce the series resistance of CZTSe or CZTSSe solar cells to a level as low as that of world-record CIGS solar cells (below ≈0.5 Ω cm 2 ), [ 14,15 ] one approach is to control the formation of MoSe 2 /MoS 2 interfacial layer between absorber and Mo back contact.…”
Section: Doi: 101002/aenm201402178mentioning
confidence: 99%
“…The formation of MoS 2 at the interface between Mo and CZTS was detected in the films sulfurized at lower pressure. The MoS 2 layer may be helpful as an electrical quasiohmic contact and can improve the adhesion between CZTS and Mo back contact but it can also lead to a high series resistance if it is not thin enough [37].…”
Section: Resultsmentioning
confidence: 99%